2019
DOI: 10.24123/mpi.v2i4.2184
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Carica papaya Seed Extract on Diabetic Rat Model with Muscle Atrophy

Abstract: This study aims to prove that papaya seed extract has the potential to improve muscle cell atrophy in diabetic conditions. Type 2 diabetes mellitus (DM) animal model were made with conditions similar to type 2 DM in humans i.e. with long-term (56 days) high sugar (fructose) consumption. Then, the next 14 days were treated with papaya seed extract at the dose of 100, 200, and 300 mg/kg BW orally. Body weight and blood glucose levels were monitored throughout the study period. At the end of the study, histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In foods, the fruit has been advantageously used as a nutritional supplement [10], appetizer [11], and snack [12], whereas as an herbal medicine, the leaves have been utilized in antimicrobe [13], antioxidant [14], antivirus [15,16], haematology disorder treatment [17], and antitumor applications [18]. Although it is minor, the papaya seeds have been studied for their antidiabetic activity [19]. In non-food and non-medicine applications, papaya leaves are also used as a bioherbicides [20], ectoparasite controls [21], and larvicides [22], as well in the control of the onion pest Spodoptera exigua [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In foods, the fruit has been advantageously used as a nutritional supplement [10], appetizer [11], and snack [12], whereas as an herbal medicine, the leaves have been utilized in antimicrobe [13], antioxidant [14], antivirus [15,16], haematology disorder treatment [17], and antitumor applications [18]. Although it is minor, the papaya seeds have been studied for their antidiabetic activity [19]. In non-food and non-medicine applications, papaya leaves are also used as a bioherbicides [20], ectoparasite controls [21], and larvicides [22], as well in the control of the onion pest Spodoptera exigua [23].…”
Section: Introductionmentioning
confidence: 99%
“…In diabetes-related applications, papaya seed extract was investigated in terms of its role in increasing glucose transporter 4 (GLUT 4) expression in the skeletal muscle cells of diabetic rats, thereby increasing glucose uptake into cells. With this increased expression of GLUT 4 in muscle cells, it was found that it could be expected to prevent cell atrophy [19].…”
Section: Introductionmentioning
confidence: 99%